Teaching Staff Strength (TSS) and Workload In Public Senior Secondary Schools In Ogba/Egbema/Ndoni Local Government Area of Rivers State, Nigeria - Nkweke , G. O; Dollah, S. A (Richtmann Publishing, 2011)
The attainment of effective education by the educatee is hinged on the balancing of the workload and the teaching staffstrength (TSS) in schools. The interplay was the rallying point of this study which tried to ascertain the level of workload andteaching staff strength (TSS) in public senior secondary schools. Six (6) research questions were posed as guide with thequestionnaire as a base instrument for data collection from the principals of the 18 public senior secondary schools in Onelga.Analysis of data on teacher-students ratio reveal that 11 schools representing 61% have a ratio above 1:40 and 7 schoolsrepresenting 39% have a ratio below 1:40 as enshrined in the FRN (2004). The class size indicates that 7 schools havemoderate class sizes whereas 11 schools have excess class sizes. Consequently the workload data analysis reveals that all theschools exceeded the 15 weekly periods per teaching staff with 17% having 18-23 while 83% having 24-30 per teacher perweek. Female teachers occupied 21% and male teachers occupied 79% of the total population of 152. The implication is thatexcess workload will affect the output been churned into the tertiary institutions. Recommendation were made among others toimprove the condition of service and track down the rate of attrition